A disciplina de Environment and Human Development para crianças de um colégio com programa bilíngue: o ensino de línguas por projetos - Franchi, Ana Bacciotti (2019)
This study investigates how the Environment and Human Development (EHD) school subject contributes Language Teaching through Projects (EAL) Teaching in Elementary School classes in a Bilingual Program at a school. Taking into consideration that this school subject is founded on a Teaching through Projects basis and is inserted in the bilingual curriculum, some research questions served as a starting point for this study: How, is the Environment and Human Development school subject developed via Language Teaching through Projects? How does this pedagogical practice contributes for Language Teaching in a school with a Bilingual Program? The term ‘project’ overlaps distinct theories, like the Project Method, Project Work, Project Pedagogy, and Project Strategies. However, these theories don´t satisfy the needs found in the observed practice, for this reason, I chose the term Teaching through Projects, relating it to the ideas of Language Teaching in the present era, which results in Language Teaching through Projects (LTP). For this study, I opted to do the data collection and data analysis on a qualitative-interpretivist research perspective: a Case Study. Methodologically, some data collection tools were used, such as the non-participant observation, field journal, teachers questionnaires, interviews and documentary sources. After the collection, the data was triangulated, discussed and analyzed. Finally, it was found that EAL Teaching in the EHD school subject, on a Teaching through Projects basis, contributes to significant learning. Therefore, this study may contribute to the advance of discussions about the importance of developing Language Teaching through Projects since it allows the relation between theory and practice and enables language learning through experience and understanding of reality.